THE RELEVANCE OF USING ARTIFICIAL INTELLIGENCE FOR EARLY-STAGE DETECTION OF PSYCHOEMOTIONAL DISORDERS IN STUDENTS - Dubrovina, Angelina (Veredas do Direito, 2026)
The learning process causes anxiety in students due to information overload and competition, increasing the risks of mental disorders. It is necessary to introduce technologies capable of promptly identifying disorders and providing personalized assistance. Special attention is paid to AI chatbots that analyze the psychoemotional state and provide anonymous support, which is necessary for students who have difficulties in communication. The study shows the effectiveness of AI methods in comparison with traditional ones. Aim. To evaluate the effectiveness of machine learning algorithms for analyzing data on the psychoemotional state of students and to compare the results of automated diagnostics with the conclusions of expert psychologists. Materials and methods. The study used analytical methods, including data processing using machine learning algorithms, an empirical research method based on a survey of a significant number of respondents and used to obtain information about what served as a factor in the emergence of psychoemotional disorders in students, and a theoretical analysis of pedagogical and psychological literature was conducted. To collect data on the psychoemotional state of students, a survey of students was conducted, and based on it, the advantages and disadvantages of artificial intelligence tools that provide anonymous interaction and regular monitoring of stress levels were identified. Results of the study. Comparison of AI and classical methods showed that algorithms detect disorders with accuracy close to expert level. Key factors: high academic load, social isolation, lack of support. Recommendations for the integration of AI have been developed, including chatbots for anonymous diagnosis and monitoring. Automated methods complement traditional ones, especially when resources are scarce, reducing stigmatization and increasing the accessibility of care. Discussion of the results. AI increases the accessibility and quality of psychological care in education. Chatbots promptly detect disorders, offer personalized support and anonymous real-time interaction, which is important for students who avoid communication; digital services are also financially more accessible than in-person consultations for the detection and correction of psychoemotional disorders.